Novel cascaded switched-diode five level inverter for renewable energy integration - Ghughuloth, Dhasharatha; Varma, Nampally Rajashekar; Adwaith, Donda; Hussain, Shakeer; Gundoji, Karthik; Samineni, Harshini (International Journal of Advances in Applied Sciences, 2024)
This research presents the usage of a unique five-level cascaded switching diode for medium voltage integration of renewable energy sources. Its primary purpose is to decrease the quantity of gate drivers and switches. In addition to that, the cost and space for the installation of multilevel inverters are less. The inverter topology of novel cascaded multilevel inverters and switched diodes will combine both benefits. One-cycle control (OCC), which is used for clock phase-shifting (CPS) to regulate a two-stage container security device (CSD) multilevel inverter of renewable energy integration, was created to address issues with the multilevel inverter's direct current (DC) source variations. The topology also provides efficiency, harmonic distortion reduction, and voltage output quality. Waveforms are created, and a robust resistance to DC source variations is attained. The viability of the unique five-level inverter using cascaded switched diodes is confirmed by discussing the results of both simulation and experiment.